STRATEGI PENDIDIKAN IBADAH SISWA DI SMP NEGERI PEUREULAK - Muhammad Juanis (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2020)
Abstract The problem in this study is that students are still lacking in worship, especially less discipline in performing congregational prayers at school, and there are even students who do not pray. Even though they are being educated and given knowledge so that they become good people and are able to carry out Allah's commands. The purpose of this study was to determine teacher policies in providing worship education to students at SMPN Peureulak, to find out the methods used by teachers in providing worship education for students at Peureulak Junior High School and the constraints of teachers in providing worship education for students at SMPN Peureulak. This study uses a qualitative method with a descriptive approach, the data sources in this study are primary data, directly from the research location, through interviews with informants, and secondary data sources in the form of documentation and official archives that support this research. The data collection techniques were collected by means of observation, in-depth interviews and documentation study. The findings in this study are that teachers have policies in providing religious education to students at Peureulak Junior High School. The policies carried out by the teacher are: 1. Always tell students to pray in congregation at the mosque during duhur time, 2. The teacher also always arrives on time in their attendance at school, 3. Controls students to perform congregational prayers, 4. Requires students to pray in congregation at the time zhuhur, 5. Make school rules about congregational prayer. However, in its implementation, this policy is still not optimal, because in reality there are still students who do not pray in congregation. Abstrak Permasalahan dalam penelitian ini adalah siswa masih kurang melakukan ibadah terutama kurang kedisiplinan melaksanakan shalat berjamaah di sekolah, dan bahkan masih ada siswa yang tidak melaksanakan shalat. Padahal mereka sedang dididik dan diberikan pengetahuan agar mereka menjadi orang baik dan mampu melaksanakan perintah Allah swt. Tujuan dari penelitian ini adalah untuk mengetahui kebijakan-kebijakan guru dalam memberikan pendidikan ibadah pada siswa di SMPN Peureulak , mengetahui metode yang digunakan guru dalam memberikan pendidikan ibadah bagi siswa di SMPN Peureulak serta kendala guru dalam memberikan pendidikan ibadah bagi siswa di SMPN Peureulak . Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, sumber data dalam penelitian ini adalah data primer, langsung dari lokasi penelitian, melalui wawancara dengan informan, dan sumber data sekunder berupa dokumentasi serta arsip-arsip resmi yang mendukung penelitian ini. Adapun teknik pengumpulan data dikumpulkan dengan cara observasi, wawancara mendalam dan studi dokumentasi. Temuan dalam penelitian ini adalah guru memiliki kebijakan dalam memberikan pendidikan ibadah pada siswa di SMPN Peureulak . Kebijakan yang dilakukan guru adalah: 1. Selalu menyuruh siswanya untuk shalat berjamaah di masjid dalam waktu duhur, 2. Guru juga selalu datang tepat waktu dalam kehadirannya di sekolah, 3. Mengontrol siswa melaksanakan shalat berjamaah, 4. Mewajibkan siswa melakukan shalat berjamaah pada waktu zhuhur, 5. Membuat peraturan sekolah tentang shalat berjamaah. Namun demikian dalam pelaksanaannya kebijakan ini masih kurang maksimal, karena dalam realitanya masih ada siswa yang tidak melaksanakan shalat berjamaah.